2019
DOI: 10.1021/jacs.9b09326
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroalkylative Activation of CNN- and PNN-Pincer Ruthenium Catalysts for Ester Hydrogenation

Abstract: Ruthenium−pincer complexes bearing CNN-and PNN-pincer ligands with diethyl-or diisopropylamino side groups, which have previously been reported to be active precatalysts for ester hydrogenation, undergo dehydroalkylation on heating in the presence of tricyclohexylphosphine to release ethane or propane, giving five-coordinate ruthenium(0) complexes containing a nascent imine functional group. Ethane or propane is also released under the conditions of catalytic ester hydrogenation, and time-course studies show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 101 publications
5
74
0
Order By: Relevance
“…Dihydride species such as g, g1, and g2 are predicted to be key intermediates, but are less stable by several kcal/mol and are expected to have low steady-state concentrations once even small amounts of alcohol product build up in ester hydrogenation reactions. We previously demonstrated (Scheme 2) that the precatalyst RuPNN imine converts quantitatively to the dihydride RuPNN HEt under hydrogen pressure, 9 although the reversibility of this reaction on removal of hydrogen prevented easy isolation of RuPNN HEt . Recently, Gusev reported a clever method to isolate the dihydride product RuPNN H2 formed by reaction of Milstein's original precatalyst RuPNN dearom with hydrogen: a solution of the dearomatized species was placed under hydrogen in an unstirred pressure vessel, in a solvent mixture that dissolved RuPNN dearom completely but allowed the product dihydride to crystallize.…”
Section: Synthesis Of Proposed Intermediatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dihydride species such as g, g1, and g2 are predicted to be key intermediates, but are less stable by several kcal/mol and are expected to have low steady-state concentrations once even small amounts of alcohol product build up in ester hydrogenation reactions. We previously demonstrated (Scheme 2) that the precatalyst RuPNN imine converts quantitatively to the dihydride RuPNN HEt under hydrogen pressure, 9 although the reversibility of this reaction on removal of hydrogen prevented easy isolation of RuPNN HEt . Recently, Gusev reported a clever method to isolate the dihydride product RuPNN H2 formed by reaction of Milstein's original precatalyst RuPNN dearom with hydrogen: a solution of the dearomatized species was placed under hydrogen in an unstirred pressure vessel, in a solvent mixture that dissolved RuPNN dearom completely but allowed the product dihydride to crystallize.…”
Section: Synthesis Of Proposed Intermediatesmentioning
confidence: 99%
“…4d, 7 During mechanistic studies of our previously reported 7c, 7d, 8 CNN-pincer-ruthenium catalysts for ester hydrogenation, we made a surprising observation: precatalysts featuring NEt2 or N i Pr2 side groups underwent an unexpected dehydroalkylation reaction, releasing an equivalent of ethane or propane early on in catalytic reactions. 9 The observation of catalytic induction periods concomitant with the release of alkane established that dehydroalkylation was a necessary step in formation of the active catalyst. Milstein's catalyst RuPNN dearom , which features an NEt2 side group, also showed an induction period for ester hydrogenation, and released ethane concomitantly with the onset of catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…In a follow‐up study, two complexes of type 87 were used to synthesize NHC‐pyridine‐imine pincer complexes (Scheme 30). [46] The same products can be produced via another approach, that is the “roll‐over” synthesis of 88 . In a comparative catalytic study of 87 – 89 in ester hydrogenation, it was verified that pincer complexes with amine arms undergo dealkylations generating generally more active catalysts.…”
Section: Nhc Employed As An Arm Donormentioning
confidence: 99%
“…Interestingly, solutions of the Ru(0) derivative 8 were active in the hydrogenation of N-heterocycles. 14,15 Thus, THF-d 8 solutions containing this complex were able to hydrogenate (3 bar H 2 ) 2-methylquinoxaline (10 equiv.) at 60°C, being 8 the only detectable metal species during the catalytic reaction and suggesting that this is the catalyst resting state (ESI †).…”
mentioning
confidence: 99%
“…14 The 1 H NMR spectrum of the resulting dark blue solutions indicates the presence of the imine moiety by the appearance of a doublet at 7.92 ppm ( 4 J HP = 3.7 Hz). The 13 C{ 1 H} NMR spectrum presents the resonances 14 These derivatives (such as A), which were shown to be highly active ester hydrogenation catalysts, were isolated from the reactions with base of Ru-PNN and -CNN complexes bearing dialkylamino side donors. Moreover, hydrogen activation by A led to the formation of a Ru dihydride complex (B) in which the imine ligand fragment was hydrogenated to amine.…”
mentioning
confidence: 99%